Efecto de la suplementación de nucleótidos purificados en dietas de pre inicio e inicio sobre los índices productivos del pato muscovy (Cairina moschata.) - Barrantes Castro, Jorge Luis (2015)
This research was conducted in the company SLLC EIRL Agricultural Investment located in the district of Laredo province of Trujillo, La Libertad, in order to determine the effect of the addition of purified nucleotides in feed on performance of muscovy duck. T1: control, T2: 0.025% nucleotide T3: 0.050% nucleotide and T4: 80 randomized BB ducks under a RCB design with two blocks (sex duck) and four treatments utlizaron from 0.050 to 0.025% nucleotide in the stages of pre startup and in the diets of ducks. For statistical analysis were used, the corresponding ANOVA design, the weights in the 11th week of age highly significant differences between treatments were calculated, with treatment 4 which reached the top weights in males at 4.31 kg in females 2.49 kg and 3.68 kg total; with respect to the other treatments (p <0.01). Treatment 4 scored higher total weight gain with 3.64 kg, followed by 3.57 kg, 3.48 kg and 3.30 kg treatments 3, 2, 1; respectively (p <0.01). As for gains weight by sex, males had a weight of 4.01 kg, higher than females with a weight of 2.36 kg (p <0.01). Treatment 2 achieved a numerically higher feed intake, 11.76 kg, determined no statistical differences between treatments (p> 0.05). Moreover, statistically significant differences (p <0.01) between the food intakes of males and females (11.49 kg vs 10.13 kg) were determined. Feed conversion between treatments ranged from 3.76, 3.39, 3.5, 3.23, for treatments 1, 2, 3, 4 respectively for males and females, and 2.84 and 4.07, respectively (p <0.01). The percentage of mortality was statistically similar for the four treatments (p> 0.05). In the index of Productive Efficiency, treatment 4 scored better response with 139, followed by treatment 2 126.7, T3 and T1 with 125.8 and 104.2 respectively. Treatment 4 had the best cost-benefit ratio, with a value of 1.28 followed by T3, T2 and T1, with rates of 1.25, 1.22 and 1.21; respectively. It is concluded that feeding diets Muscovy ducks Pre Start - 0.05% Nucleotides, Home - Nucleotides 0.025%, Growth and Fattening - Basal improves growth performance of ducks to the eleventh week of age.